Novelizovaný zákon o cenných papieroch
Zákon č. 600/1992 Zb. o cenných papieroch v znení zákona NR SR č. 88/1994 Z.z., zákona NR SR č. 246/1994 Z.z., zákona NR SR č. 249/1994 Z.z., zákona NR SR č.171/1995 Z.z., zákona NR SR č. 304/1995 Z.z., zákona NR SR č.58/1996 Z.z., zákona NR SR č. 373/1996 Z.z., zákona č. 204/1997 Z.z., zákona č. 144/1998 Z.z. a zákona č. 128/1999 Z.z.